The effect of pauh kijang (Irvingia malayana Oliv ex. A. Benn) in decreasing parasitemia percentage in mice infected with Plasmodium berghei - PRAPTIWI PRAPTIWI; CHAIRUL CHAIRUL (Biodiversitas Journal of Biological Diversity, 2008)
This study was conducted to determine the influence of pauh kijang (Irvingia malayana Oliv.) stem bark ethanol extract in decreasing parasitemia in mice infected with Plasmodium berghei. Mice were divided into 6 groups as treatments: (1) negative control (CMC), pauh kijang ethanol extract with the concentration of (2)1, (3)10, (4)100, (5) 1000 mg/kg BW, and (6) quinine as positive control. The result showed that meridian effective dose (ED50) of pauh kijang ethanol extract was 36.95 mg/kg BW. Treatment of 100 mg/kg BW lowered parasitemia level by 63.8%, and this treatment did not give significant different (P>0.05) compared to positive control. The result suggests that pauh kijang ethanol extract had antiplasmodial activity since this extract reduces parasitemia more than 30%.Â© 2008 Jurusan Biologi FMIPA UNS SurakartaKey words: Irvingia malayana, antimalarial, malaria, ED50, plasmodium